Atuação profissional em casos de Síndrome de Wilkie: uma revisão da literatura - Lima Costa, Renata Luzia (2024)
Wilkie Syndrome is a rare syndrome, which has congenital or acquired etiology and is caused by obstruction of the third duodenal portion, which is compressed by the superior mesenteric artery. Its signs and symptoms are progressive and may include intermittent vomiting, nausea and generalized pain in the abdominal region and, therefore, can be confused with other pathologies. Therefore, the objective of this study is to discuss professional performance in cases of Wilkie syndrome. In view of such information, it is valid to conclude the relationship between its rarity and the risk it presents, given the difficulty in diagnosis and its similarity with other diseases. It can be detected through imaging tests such as: tomography, X-ray with Barium and Endoscopy, with X-ray with the aid of Barium being the most efficient and the majority of cases resolved through surgical intervention, performing the deviation of the part obstructed. Despite the relevance of the topic in professional practice in cases of Wilkie's syndrome, there are few studies that address the issue, which requires the development of updated studies on the disease, enabling adequate management and early recovery of the patient, without present unnecessary injuries.